Physical properties of greenhouse container media - Nelson, Gary Charles, author; Hartley, David E., advisor; Goldsberry, Kenneth L., committee member; Danielson, Robert E., committee member; Hanan, Joe J., committee member (Colorado State University. Libraries, 1976)
Combinations of Canadian peat, vermiculite, perlite, Colorado peat, sand and soil were used to prepare 50 greenhouse container media. These media were placed in six-inch plastic pots in a greenhouse environment. Physical properties were determined on undisturbed core samples taken from these pots at 0, 30, 60 and 90 days after potting. There were no changes in bulk density or total porosity over a 90-day period and only slight changes in aeration porosity and available water. Aeration porosities of the media ranged from 18-54%, all values being above the 10-15% minimum recommended by most researchers. Fresh and dry weights of chrysanthemums grown in 10 widely varying media increased with increasing aeration porosity. Available water ranged from 16-57%. Media with a high percentage of Canadian peat, Colorado peat, or vermiculite held the greatest amounts of available water and those high in soil or sand held the least. Bulk densities ranged from 0.10-1.55 g/cc. If densities less than 1.0 g/cc are desired, less than 80% soil or 60% sand should be used. Total porosities ranged from 43-97% and were correlated with all other physical properties. Bulk density values can be used to predict the total porosity of media. Total porosity values may be used to approximate available water and give a general idea of aeration porosity. In general, soilless media possessed the most desirable physical properties. Media containing only soil and/or sand consistently had the least desirable properties. Adding sand to soil produces few, if any, physical improvements. Colorado peat appears satisfactory as a substitute for Canadian peat. Physical properties of Colorado peat are more desirable when mixed with perlite or vermiculite, rather than soil or sand. The threshold proportion concept did not apply to any of the physical properties for most of the media tested.
Covers not scanned.
Keywords: Soils -- Composition; Greenhouse management